I am still a bit confused by how to convert into CNF even though I have the rules written down.
How do I convert the following sentence into CNF?
$(I \lor M) \Rightarrow H$
I know I need to get rid of the implication symbol and when its in the form $(I \Rightarrow H)$ or $(M \Rightarrow H)$ then I can see how to do it, but when its one sentence like this how do I factor out the implication?
The reason I am stuck is because I do not know how to get rid of the resulting or:
$(\neg I \lor H) \lor (\neg M \lor H) \Rightarrow I$ think the OR here needs to be an AND to be CNF